2021
DOI: 10.21203/rs.3.rs-477964/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Process-related impurities in the ChAdOx1 nCov-19 vaccine

Abstract: Sinus venous thrombosis has been linked to immunization with the ChAdOx1 nCov-19 vaccine. The initial trigger for this serious adverse event has not been determined. We analyzed the ChAdOx1 nCov-19 vaccine by biochemical and proteomic methods. We found that the vaccine, in addition to the adenovirus vector, contains substantial amounts of both human and non-structural viral proteins. Among the human proteins, heat-shock proteins and cytoskeletal proteins were particularly abundant. The often-observed strong cl… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…As far as we know, the differences between the vaccines are as follows: 1) The type of adenovirus is different (human Ad26 and chimpanzee adenovirus in the AD26 and ChA vaccines, respectively); 2) the human cell lines by which adenovirus are produced are different: T-REx-293 cells for ChA and PER.C6 TetR cells for AD26 [ 44 ]; 3) ChA contains a large number of host cell proteins differently from AD26 [ 10 , 44 , 45 ]; 4) chimpanzee adenovirus has a stronger negative charge than human AD26 [ 40 ]. Molecular simulations suggest that the chimpanzee adenovirus charge, combined with aspects of the virus shape, could allow it to bind to the positively charged PF4 protein [ 46 ]; 5) The number of viral particle in the AD26 vaccine is 3.3-fold higher than that in the ChA vaccine [ 47 , 48 ], possibly implying a higher spike protein and adenoviral protein burden.…”
Section: Discussionmentioning
confidence: 99%
“…As far as we know, the differences between the vaccines are as follows: 1) The type of adenovirus is different (human Ad26 and chimpanzee adenovirus in the AD26 and ChA vaccines, respectively); 2) the human cell lines by which adenovirus are produced are different: T-REx-293 cells for ChA and PER.C6 TetR cells for AD26 [ 44 ]; 3) ChA contains a large number of host cell proteins differently from AD26 [ 10 , 44 , 45 ]; 4) chimpanzee adenovirus has a stronger negative charge than human AD26 [ 40 ]. Molecular simulations suggest that the chimpanzee adenovirus charge, combined with aspects of the virus shape, could allow it to bind to the positively charged PF4 protein [ 46 ]; 5) The number of viral particle in the AD26 vaccine is 3.3-fold higher than that in the ChA vaccine [ 47 , 48 ], possibly implying a higher spike protein and adenoviral protein burden.…”
Section: Discussionmentioning
confidence: 99%
“…Building on this idea, one study found that the Oxford/AstraZeneca vaccine could bind with PF4 and induce pro-inflammatory immune responses at the site of injection 149 . Additionally, two studies have found significant levels of protein-based impurities in the Oxford/ AstraZeneca vaccine, including heat-shock proteins 149,150 . Such impurities may also contribute to immunological reactions to the vaccine and may help explain differences in VIT rates between the major approved Ad vaccines, assuming each vaccine uses a slightly different purification process.…”
Section: Vaccine Induced Thrombocytopenia (Vit)mentioning
confidence: 99%
“…Related to Heparin induced thrombocytopenia (HIT) it has been reported that the induction of anti-PF4 autoantibodies and platelet activation in a subset of patients, may result in the observed combination of thrombocytopenia and thromboses mainly in large vessels including cerebral venous sinus and (Figure 11, left side). Additionally, it is possible that protein impurities from the vaccine production process may be involved in the generation of a pro-inflammatory status (16). Here we propose a third pathomechanism as it is depicted in Figure 1, right side.…”
Section: Discussionmentioning
confidence: 78%